Analysis of fundamental dependencies between manufacturing and processing Tailored Blanks in sheet-bulk metal forming processes. (2017) - Schulte, R.; Hildenbrand, P.; Vogel, M.; Lechner, M.; Merklein, M.
Abstract: Forming of parts with thick-walled functional elements out of sheet metal requires innovative manufacturing methods and a fundamental and holistic process understanding. The sheet-bulk metal forming process applied in this investigation is a single-stage combination of deep drawing and upsetting. It enables the manufacturing of cups with circumferentially arranged functional elements, such as gears or carrier geometries. The basic geometry is formed in a deep drawing operation. During the subsequent upsetting, the gearing is manufactured. Potentials and limitations for the application of conventional blanks were identified, the interactions between process parameters and semi-finished product properties were analyzed and the influence on part properties was quantified. Previous investigations have shown that the application of blanks with a varying sheet thickness is expedient to enable improved die filling and preventing the grooving of the cup wall as well as the radial material flow from the cup wall into the bottom of the cup. However, material thinning at the drawing punch radius induces folding of the material in the upsetting process. To prevent such process failures and improve the properties of the final component, a process adapted blank geometry was identified. The Tailored Blanks are experimentally manufactured in an orbital forming process and resulting effects on the properties of the functional component are investigated. In this context, an analysis of geometrical and mechanical properties of both Tailored Blanks and functional components is the prerequisite for a deeper process understanding in sheet-bulk metal forming.